SDG 2 – ending hunger: the effect of Nigeria’s land titling on production output and food security of farming households - Adeyemo, Temitayo Adenike; Adeagbo, Adeola Oluwabunmi (Frontiers in Sustainable Food Systems, 2024)
Achieving zero hunger is intricately linked to sustainable agricultural production and the workings of a farming system. With land being the most important resource in smallholder agriculture in developing countries; including Nigeria; the effect of legal land ownership is a sine qua non for the process of achieving zero hunger in Nigeria. This study examined Nigeria’s attempt at making agricultural land both accessible and utilizable for smallholders in Nigeria through the Presidential Technical Steering Committee on Land Reforms in 2009. The aim was to explore the extent to which land ownership had become legalized; so that it had positive investment incentives for smallholder farmers to improve their investment portfolio on their holdings. A secondary dataset of 4,032 respondents obtained from the Living Standard Survey Integrated Survey on Agriculture (LSMS/ISA) of the 2018/2019 season, was used for the study. Data analysis included descriptive statistics and a 2-stage least square model. The apriori being that legal land ownership provided a perception of security that would enhance farm-level investment; which would therefore increase production output and hence food security. The findings revealed that although land titling was low ( 12%) within the agricultural system; its return on production output was highly significant (5.3; p < 0.05). The possession of land title would also increase per capita food consumption expenditure (0.35; p < 0.05) among the farming households. On average, households with access to land titles had a significantly higher (at p < 0.01) food expenditure (N9, 868.00) than those without land titles (N6171.72). Other farm-level investment variables such as credit use, and mechanization through tractor use were significant in improving food security amidst the security presented by possession of land title. Thus, expediting the implementation and coverage of formal land registration and titling may be a first step to contributing meaningfully to the food security drive of the SDGs in Nigeria.